Root coverage of a maxillary lateral incisor with gingival recession, gingival stillman’s cleft, bony exostosis, and denture stomatitis: a case report with 3-year follow-up - Chengjie Xie; Yeungyeung Liu; Huimin Yu; Jie Mei (BMC Oral Health, 2022)
Abstract Background Coronally advanced flap combined with connective tissue graft is considered as the golden standard of root coverage. Although Miller class I recession is considered to get complete root coverage, there are some uncommon conditions in different cases. This case reported a maxillary lateral incisor with a gingival recession, a stillman’s cleft, a bony exostosis and a denture stomatitis. Case presentation A 27-year-old female with a gingival recession, a stillman’s cleft and a bony exostosis was treated by coronally advanced flap combined with connective tissue graft technique, and the complete coverage was achieved. Later a denture stomatitis occurred when an acrylic removable partial denture was used, however the gingival margin was not affected. The denture stomatitis disappeared when a new denture with casting palatal plane was produced. In this case of 3-year follow-up, the gingival contour remained stable and the outcome was satisfactory. Conclusion Coronally advanced flap combined with connective tissue graft technique is a classic manner to treat gingival recession especially for a long term stability, even when there is a gingival stillman’s cleft, a bony exostosis and a denture stomatitis.